No Viral No Justice sebagai Model Baru Pendekatan dan Penyelesaian Hukum di Era Digital - Moh Sa’diyin; Sutopo, Sutopo (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
It is important to develop programs that focus not only on technical skills, but also on the formation of critical and ethical attitudes in the use of social media to achieve more substantial justice. An effective digital literacy program should include training for people to understand their legal rights, as well as encouraging active participation in more equitable law enforcement. A comprehensive digital literacy program will help people understand their legal rights and how to actively participate in more effective and equitable law enforcement. The method used in this study is a qualitative research method of description using phenomena as the main case material. Literature studies are also used to dissect social phenomena that are occurring. Our primary and secondary data are obtained from materials in the form of books, journals, magazines and other sources in the form of data from the internet. The program must also involve various elements, including academics and law enforcement officials, to ensure sustainability and effectiveness in improving people's digital literacy, especially in the face of legal challenges in the digital era. A comprehensive digital literacy program must also pay attention to the specific needs of the community in order to provide maximum benefits in the law enforcement process. Thus, this research has the potential to make a significant contribution to understanding the dynamics between social media and law enforcement, as well as driving the improvements needed to achieve more substantial justice. Effective digital literacy programs will encourage people to better understand their legal rights and actively participate in more equitable and responsive law enforcement in the digital age. It is important to continue to develop adaptive digital literacy programs, so that people can better respond to legal challenges in the digital era and contribute to substantial justice. It is important to create better legal awareness in the community so that they can actively participate in more effective and fair law enforcement.